1993
DOI: 10.1002/cyto.990140413
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood method for simultaneous detection of surface and cytoplasmic antigens by flow cytometry

Abstract: Dual parameter analysis of surface antigens in flow cytometry has become a standard method for detection of cell subsets. However, few methods have been described for the extension of multiparameter analyses to include cytoplasmic or intracellular antigens. Here we describe a simple and reproducible method for simultaneous detection of surface and intracellular antigens by flow cytometry in lysed whole blood samples. This method employs the use of digitonin, a mild glycoside detergent, and formaldehyde for per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…To further validate this permeabilization method, gated lymphocytes were evaluated for the expression of the cytolytic granule-associated protein detectable with the TIA-1 antibody. Consistent with the findings of Landay et al (14), this intracellular protein was found in few CD4-positive lymphocytes (Fig. 6A) and about half of CD8-positive lymphocytes (Fig.…”
Section: Expression Of Tcr Chain In T-lymphocyte Subsetssupporting
confidence: 90%
See 2 more Smart Citations
“…To further validate this permeabilization method, gated lymphocytes were evaluated for the expression of the cytolytic granule-associated protein detectable with the TIA-1 antibody. Consistent with the findings of Landay et al (14), this intracellular protein was found in few CD4-positive lymphocytes (Fig. 6A) and about half of CD8-positive lymphocytes (Fig.…”
Section: Expression Of Tcr Chain In T-lymphocyte Subsetssupporting
confidence: 90%
“…Another in-house technique that works for detection of cytokeratin and proliferating cell nuclear antigen (PCNA), which permeabilizes and fixes cells via slow addition of ethanol to a final concentration of 60%, also was not successful for detection of the TCR chain. A published fixation/permeabilization procedure for detection of the 15-kD cytoplasmic granule-associated protein recognized by the TIA-1 antibody was not successful in detecting the TCR chain (14), but the technique described herein is able to detect the TIA-1 antigen as well as the TCR chain in T lymphocytes.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…For flow cytometric analysis, most researchers have treated corresponding cells with formalin at concentrations less than 1-2% for 4 min at 37 • C prior to staining with antibodies in order to prevent in vitro degeneration [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Detection of intracellular MPO was performed according to the Caltag (Burlingame, CA) protocol for cellular fixation and permeabilization (12)(13)(14) using the Fix & Perm cell permeabilization kit and appropriate volumes of anti-MPO (FITC-conjugated) monoclonal antibody (Caltag). An isotype control was carried out in parallel.…”
Section: Sample Preparation For Flow Cytometry Analysismentioning
confidence: 99%